(untitled) (Conference Zone, 2022)
This article discusses the reforms in the field of culture in the new Uzbekistan and their phased analysis. The article also analyzes the issues of protecting our spirituality from various harmful influences that are alien to our people in the context of globalization, turning it into an integral part of the minds, hearts and worldviews of our youth. Opinions were expressed on the prospects for the further development of cultural reforms in Uzbekistan.